Synthetic sex-aggregation pheromone of Lutzomyia longipalpis, the South American sand fly vector of Leishmania infantum, attracts males and females over long-distance - González, Mikel A.; Bell, Melissa; Souza, Cristian F.; Maciel-de-Freitas, Rafael; Brazil, Reginaldo P.; Courtenay, Orin; Hamilton, James G. C. (PLOS Neglected Tropical Diseases, 2020)
Background In South America the sand fly Lutzomyia longipalpis is the predominant vector of Leishmania infantum, the parasite that causes canine and human visceral leishmaniasis. Co-location of synthetic male sex-aggregation pheromone with an insecticide provided protection against canine seroconversion, parasite infection, reduced tissue parasite loads, and female sand fly densities at households. Optimising the sex-aggregation pheromone + insecticide intervention requires information on the distance over which female and male Lu. longipalpis would be attracted to the synthetic pheromone in the field. Methodology/Principal findings Wild Lu. longipalpis were collected at two peridomestic study sites in Governador Valadares (Minas Gerais, Brazil). Sand flies were marked with coloured fluorescent powder using an improved protocol and then released into an existing domestic chicken shed at two independent sites, followed by recapture at synthetic-pheromone host-odour baited traps placed up to 30 metres distant from the release point. In total 1704 wild-caught Lu. longipalpis were released into the two chicken sheds. Overall 4.3% of the marked flies were recaptured in the pheromone baited experimental chicken sheds compared to no marked flies recaptured in the control sheds. At the first site, 14 specimens (10.4% of the marked and released specimens) were recaptured at 10m, 36 (14.8%) at 20m, and 15 (3.4%) at 30m. At the second site, lower recapture rates were recorded; 8 marked specimens (1.3%) were recaptured at 5 and 10m and no marked specimens were recaptured at 15m. Approximately 7x more marked males than females were recaptured although males were only 2x as common as females in the released population. 52% of the marked Lu. longipalpis were collected during the first night of sampling, 32% on the second night, and 16% on the third night. Conclusions/Significance The study established that both male and female sand flies can be attracted to the synthetic sex-aggregation pheromone in the presence of host odour over distances up to at least 30m in the field depending on local environmental and meterological conditions.